Rethinking bamboo: an Asian eco-Interior design language with ecological branding in East Asia - Baniyamin, Nurhaya; Mohd. Din, Shamzani Affendy (Universitas Indraprasta PGRI, 2019)
This article takes a look and survey of the approaches in interior design possibilities and expressions in applying the use and particular structural qualities of bamboo. This particular material has gained much interest due to its quality of being rapidly replenishable, thus allowing it as an alternative to more depleting resources such as timber and other materials. The paper focuses on the higher applications of bamboo and the recent corporate space design and its typological function gain from the application of bamboo as an interior design strategy and aesthetics. With the move by the United Nation on having 17th initiatives under Sustainable Development Goals (SDGs), this study will discuss further how bamboo could be improving the quality of life in the countries with the tropical climate where bamboo vastly grown and reliable as one sustainable material in construction of structure outdoor, indoor and also to be used widely in arts & craftsmanship in the region.